Determinants of financial performance and stock value in sharia and conventional bank - Akhmad Syarifudin; Eko Darmawan Suwandi (Jurnal Ekonomi, 2024)
The COVID-19 pandemic has adversely affected the economy, leading to a decrease in the financial resources available to borrowers and the implementation of rules that restrict access to funding. The objective of this study is to analyze the factors that influence the financial performance and stock value of Sharia and conventional commercial banks that are publicly traded on the Indonesia Stock Exchange. The secondary data source consists of annual bank financial reports spanning the period from 2017 to 2021. The application of Multiple Linear Regression with SPSS and SEM is utilized in testing. The Mann Whitney Test was employed to conduct the difference test. This study discovered disparities in the factors that influence profitability and share value between Sharia and regular banks. The findings indicate that the factors CAR, FDR, BOPO, and NPL have a limited impact on the ROA of Islamic banks. Conventional banks demonstrate that the capital adequacy ratio (CAR) and the loan-to-deposit ratio (FDR) do not impact the return on assets (ROA). However, the operating expenses to operating income ratio (BOPO) and the non-performing loans ratio (NPL) have a detrimental influence on ROA. Additional research indicates that CAR has a favorable impact on the stock value of Islamic banks, but it does not have any influence on the stock value of conventional banks. Moreover, the ROA positively impacts the share value of conventional banks, while it does not have any influence on the share value of Islamic banks. In addition, the research findings indicate that the ROA does not serve as a mediator for the impact of CAR on the value of shares, regardless of whether it is in Islamic or conventional banks. Banking management must enhance control over BOPO and NPL while increasing CAR to boost profitability and share value.